EVALUASI KARAKTERISTIK FISIK DAN KIMIA COMPLETE FEED FERMENTASI BERBASIS VARIETAS SORGUM (SORGHUM BICOLOR (L.) MOENCH) DAN PERBEDAAN LEVEL PROTEIN: EVALUATION OF PHYSICAL AND CHEMICAL CHARACTERISTICS OF FERMENTED COMPLETE FEED BASED ON SORGHUM (SORGHUM BICOLOR (L.) MOENCH) VARIETIES AND PROTEIN LEVELS - Dewi, Anggi Derma Tungga; Sanjaya, Herdiyon Banu; Rahayu, Eka Rizky Vury; Suhartanto, Bambang (Tropical Animal Science, 2025)
This study was carried out to determine the effect of sorghum varieties and protein levels of fermented complete feed on physical and chemical quality on completely randomized design with a 2 x 2 factorial pattern, two varieties of sorghum forage namely BMR and Super-2 were used to make a complete feed with 2 different protein levels, 8 and 11%, then fermented for 7 days. Each treatment was in 3 replications. Fermented complete feed was sampled for physical quality, including smell, color, texture, and presence of fungus, as well as chemical quality analysis, including dry matter (DM), organic matter (OM), crude protein (CP), and crude fiber (CF). Data were analyzed for variance according to a completely randomized design with a factorial pattern, and differences between treatments were tested by Duncan's multiple range test. The results showed that the complete feed fermented sorghum of the BMR variety had better physical (color, texture, and fungus) and chemical quality (DM, OM, CP, and CF) ??(P<0.05) compared to super-2. 11% protein level of fermented complete feed had better physical (color and fungus) and chemical quality (DM, OM, CP, and CF)  ??(P<0.05) compared to the 8% protein level.